Clinical Outcomes and Complications of Primary Fingertip Reconstruction Using a Reverse Homodigital Island Flap: A Systematic Review. (March 2023) - Xu, Joshua; Cao, Jacob Y.; Graham, David J.; Lawson, Richard D.; Sivakumar, Brahman S.
Background: Reverse homodigital island flaps (RHIFs) are increasingly used to reconstruct traumatic fingertip injuries, but there is limited evidence on the efficacy of this technique. We performed a systematic review of the literature to establish the safety and functional outcomes of RHIF for traumatic fingertip injuries. Methods: Electronic searches were performed using 3 databases (PubMed, Ovid Medline, Cochrane CENTRAL) from their date of inception to April 2020. Relevant studies were required to report on complications and functional outcomes for patients undergoing RHIF for primary fingertip reconstruction. Data were extracted from included studies and analyzed. Results: Sixteen studies were included, which produced a total cohort of 459 patients with 495 fingertip injuries. The index and middle fingers were involved most frequently (34.6% and 34.1%, respectively), followed by the ring finger (22%), the little finger (6.7%), and the thumb (2.6%). The mean postoperative static and moving 2-point discrimination was 7.2 and 6.7 mm, respectively. The mean time to return to work was 8.4 weeks. The mean survivorship was 98.4%, with the pooled complication rate being 28%. The pooled complication rate of complete flap necrosis was 3.6%, of partial flap necrosis was 10.3%, of venous congestion was 14.6%, of pain or hypersensitivity was 11.5%, of wound infection was 7.2%, of flexion contractures was 6.3%, and of cold intolerance was 17.7%. Conclusions: Reverse homodigital island flaps can be performed safely with excellent outcomes. To minimize complications, care is taken during dissection and insetting, with extensive rehabilitation adhered to postoperatively. Prospective studies assessing outcomes of RHIF compared with other reconstruction techniques would be beneficial.